Microsurgery of chronic laryngeal diseases using fiber optic lasers. A review - Aleksandr A. Krivopalov; Polina A. Shamkina; Alexandra I. Glushchenko (ZAO "Consilium Medicum", 2023)
Background. The treatment of chronic diseases of the larynx is an urgent issue. Chronic larynx masses account for up to 5570% of the upper respiratory tract proliferative diseases. The incidence of vocal apparatus disorders is stable due to increased load on the vocal apparatus, neuro-emotional stress, non-compliance with voice hygiene (smoking, alcohol consumption), nasal and pharyngeal inflammatory diseases, sensibilization, and gastrointestinal disorders. Dysphonia, voice timbre changes, and vocal fatigue are presented in 712% of otorhinolaryngologist patients. Delayed treatment of chronic larynx diseases can lead to upper respiratory obstruction, reduced exercise and self-care tolerance, and disablement in people with voice and speech professions. Aim. To address current treatment methods for chronic diseases of the larynx. Modern surgical and non-surgical treatments of chronic larynx diseases aim to restore voice quality and respiratory function. Over the past 50 years, laser-assisted phonosurgery has gained popularity due to the many benefits of biological tissue exposure to electromagnetic energy and low rates of intra- and postoperative complications. Materials and methods. The literature review was performed using electronic medical libraries and professional printed papers. According to local and foreign data, laryngeal laser surgery is highly precise, minimally invasive, associated with no blood loss, and highly effective. Historically, CO2 laser has been used for the longest time in laryngeal surgery. Modern medical technology has recently introduced surgical systems with novel technicalities for clinical use. In such devices, the laser energy is transmitted through a flexible optical fiber instead of a mirror system, as in the CO2 laser, which has made new surgical high-energy systems more affordable for equipping medical institutions. Currently, the following fiber-optic laser systems are most often used to treat chronic diseases of the larynx: potassium-titanyl-phosphate, diode laser, and "blue" laser with a wavelength of 445 nm. Results. The literature review and analysis of surgical treatment outcomes using fiber-optic laser devices in patients with chronic larynx diseases showed high safety and effectiveness of modern treatments, providing fast recovery of voice and respiratory function. Conclusion. The development of laser devices, including domestic ones, with new wavelengths, makes it possible to work in contact mode in an inert gas environment, which opens up new opportunities for phonosurgery.